Active Terahertz Shielding and Absorption Based on Graphene Foam Modulated by Electric and Optical Field Excitation. Issue 18 (7th June 2019) - Xu, Shi‐Tong; Fan, Fei; Cheng, Jierong; Chen, Honghui; Ma, Wenle; Huang, Yi; Chang, Shengjiang
Abstract: Ultralight materials for broadband terahertz (THz) shielding and absorption are promising in practical THz applications. Here, active THz shielding and absorption properties of 3D graphene foam (GF) controlled by both laser pumping and biased electric field are investigated. The GF can be tuned from OFF‐shielding state to ON‐shielding state when the external field excitations are applied, and 10 dB shielding bandwidth expands from 0 to a broad band of 0.2–1.6 THz. Further researches show that the GF always keeps very low THz reflection either with or without external fields, but its absorption characteristics can be remarkably controlled from 13% to 95.4% at 0.3 THz by the power of the external excitations, and its specific average terahertz absorption performance increases from 3.9 × 10 3 to 1.95 × 10 4 dB cm 3 g −1 . This modulation mechanism reveals that the carrier density in GF increases one order of magnitude from 2.6 × 10 14 cm −3 to 3.15 × 10 15 cm −3 . Finally, the tunable THz shielding and absorption characteristics of this GF device are demonstrated by THz transmission imaging, which shows its great potential applications in active THz imaging, radar, and electromagnetic compatibility. Abstract : The active THz shielding and absorption properties of 3D graphene foam are investigated by both the laser pumping and biased electric field. THz imaging demonstrates that it can be tuned from OFF‐shielding state to ON‐shielding state when the external field excitations are increased from 0 to the highest level.